Primary Life Stage Boron Isotope and Trace Elements Incorporation in Aposymbiotic Acropora millepora Coral under Ocean Acidification and Warming - Wu, Henry C.; Dissard, Delphine; Le Cornec, Florence; Thil, François; Tribollet, Aline; Moya, Aurelie; Douville, Eric (Frontiers in Marine Science, 2017)
Early-life stages of reef-building corals are vital to coral existence and reef maintenance. It is therefore crucial to study juvenile coral response to future climate change pressures. Moreover, corals are known to be reliable recorders of environmental conditions in their skeletal materials. Aposymbiotic Acropora millepora larvae were cultured in different seawater temperature (27 and 29ºC) and pCO2 (390 and 750 µatm) conditions to understand the impacts of ‘end of century’ ocean acidification (OA) and ocean warming (OW) conditions on skeletal morphology and geochemistry. The experimental conditions impacted primary polyp juvenile coral skeletal morphology and growth resulting in asymmetric translucent appearances with brittle skeleton features. The impact of OA resulted in microstructure differences with decreased precipitation or lengthening of fasciculi and disorganized aragonite crystals that led to more concentrations of centers of calcifications. The coral skeletal δ11B composition measured by laser ablation MC-ICP-MS was significantly affected by pCO2 (p = 0.0024) and water temperature (p = 1.46 x 10-5). Reconstructed pH of the primary polyp skeleton using the δ11B proxy suggests a difference in coral calcification site and seawater pH consistent with previously observed coral pH up-regulation. Similarly, trace element results measured by laser ablation ICP-MS indicate the impact of pCO2. Primary polyp juvenile Sr/Ca ratio indicates a bias in reconstructed sea surface temperature (SST) under higher pCO2 conditions. Coral microstructure content changes (center of calcification and fasciculi) due to OA possibly contributed to the variability in B/Ca ratios. Our results imply that increasing OA and OW may lead to coral acclimation issues and species-specific inaccuracies of the commonly used Sr/Ca-SST proxy.